Ver e compreender : literacia visual e interfaces de telemóveis - Araújo, Mariana, 1989- (2014)
The main goal of this work is to measure the importance of visual literacy as a relevant competence for the comprehension of visual information. The study, empirically based, explores the influence of visual literacy in the recognition and interpretation of icons through tests applied to mobile interfaces. From the examination of two samples of individuals with different degrees of visual literacy, the research seeks to verify differences in the recognition of icons and even establish which are more easily seized and those who are more difficult to perceive. Based on the principle that the effectiveness of an icon lies in its ability to be quickly and correctly interpreted and understood, and assuming that this decoding also depends, on the behalf of the user, on a personal, cultural and subjective process, the study consists in a set of tests - of association, comparative and timed – that aim at comparing the perceptual and cognitive competence of the two samples, while weighting the effect of a prior familiarization with the interface. The results of this study suggest the existence of gaps in relation to visual literacy, especially in the group of individuals not entitled to specific learning in the field of visual arts. This is a reduced and limited scale project regarding the extrapolation of its results. However, it intends to serve as a starting point for future studies that are aiming to deepen the theme of visual literacy. In the current context, considering that the new media have an increasingly complex visual nature, the work highlights the growing importance of the visual stimulus and the need of proper tools for an effective and complete interpretation of these means, which leads to greater accountability of the areas that can contribute to the increase of visual literacy of the populations. This study highlights the possible benefit that some adjustments of the academic curricula, based on a more visual education, can bring towards a more efficient interaction with technology and new forms of communication in society